Blunt chest trauma: Relato - Quintero, Ariel (Cirugía del Uruguay, 1974)
The modern man lives depending on time and speed. In civilian life the development of highways and fast automobiles has resulted in a great number of seriously traumatized patients. Traffic in large cities has become complex and requires experts to organize same. In 1967, in the United States there were 13 million accidents. Every ten minutes one person dies from injuries, and there is a serious politraumatized case every ten seconds. These figures speak for themselves. In cases of politraumatized patients, serious thorax injury is the most frequent. The requires a precise and immediate examination and treatment, at it has repercussion in vital functions such as respiration, and without oxigen life is lc;st in a few minutes; cardiac and circulatory functions may also be seriously impaired. An analysis made of the lack of proportion which may exist between a slight attack with great functional difficulties and, sometimes serious traumatisms with apparently important lesions can be managed -saving the life of the injured person- with a therspeutic measure such as a pleural drainage. The author then explains the functional difficulties which F1ail segments cause, being one of the more serious injuries in traumatic thorax. The problems as to tretament and risks, as well as the possible complications that rnay arise, were also discussed. Fixed Flail segments and the care that must be given the patient was mentioned, as also the constant observation in case of a possible decompensation. The present trends as to treatment, and the importance of assisted respiration was also mentioned. Then the author spoke of diaphragmatic rupture, of the difficulty of diagnosis, the permanent anxiety of a traumatized patient, as to the thype of injury and the complications that may subsequently appear. Mention was made of bronchial obstruction and rupture of the tracheobronchial tree, adding that this type of injury is deceiving and hides under the frosted glass of pneumothorax, which prevents the doctor from clearly seeing the evidence. The use of a bronchoscope is of prime importance to reach a correct diagnosis. The author goes on to describe intrathoraxic hemorrhages -hemothorax and pneumothorax- . As a physician not practicing in specialized centers, preference goes to\-vards puncture and not to drainage of hemothorax. The importance of Pi'renchyma injury, alveolar edema, hemorrhagic suffusions and its significance; lung hematoma, rupture of parenchyma are described. Thoraco-abdominal injuries, the complexity of diagnosis and the therapeutic problems that may arise, were also mentioned, but always keeping in mind that, in the face of associated injuries -unless under exceptional circumstances-'- the first thought should be for cardiorespiratory functions. Statistics revea! that the more frequent are 111Junes to herat, pericardium and spleen, and although the author does not have experience in this field, the subject is constantly in mind and the search is systematic. Injuries to esophagus and amediastinum were discussed, and to conclude an analysis was made of the principal factors for treatment, on the basis of physioptahological knowledge.